The Impact Of Teachers Non-Verbal Questioning Behavior On Student Participation In The Classroom - Asrori Asrori (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2018)
Questioning has been becoming the subject of the study since it is regarded as one of the most important ways to maintain the classroom interaction. Several studies have been carried out on the use of questions but most of them are focused on the type of questions used by the teacher. Moreover, the teacher often neglects their non-verbal behavior when they deliver questions to the students. Hence, this study investigates the impact of teachers nonverbal questioning behavior on the students’ participation. The study was conducted with teacher and students of State University of Surabaya (UNESA). The data were the conversations between teacher and students in the Reading classroom taken through video recording and observation. The result of the study shows that teacher’s nonverbal questioning behavior affects much on the students’ participation in the classroom. Maintaining eye contact to the students while asking questions gives a good effect on keeping the students participation. Moreover, the appropriate use of other nonverbal questioning behaviors such as calling the students while asking, giving a right wait time, handling the students’ answer positively, also give positive effect on the students participation.